Oil price and exchange rate nexus in Algeria: evidence from nonlinear asymmetric and frequency domain approach. Issue 5 (10th July 2021) - Chekouri, Sidi Mohammed; Sahed, Abdelkader; Chibi, Abderrahim
Abstract : Purpose: This paper aims to examine the relationship between exchange rate and oil prices in Algeria over the period 2004Q1–2019Q4. Design/methodology/approach: The nonlinear autoregressive distributed lag method is used to capture the potential asymmetric relationship among oil prices and the exchange rate. Frequency domain spectral Granger causality test is also applied to investigate the causal linkage between the two variables. The wavelet coherence is applied to analyze the evolution of this relationship both in time and frequency domains. Findings: The empirical results reveal evidence of long-run asymmetric effects of oil price on Algeria's real effective exchange rate (REER), implying that an increase in oil price causes a real exchange rate to appreciate, while a decrease in oil price leads to a real exchange rate to depreciate. More specifically, it is found that the impact of negative oil price shocks is higher than the one associated with positive shocks. The spectral Granger causality results further indicate that there is unidirectional causality running from oil price to REER in both medium and long run. The wavelet coherence findings provide evidence of some co-movement between the REER and oil price and point out that the oil price is leading real exchange rate in the medium and long terms. Originality/value: This study contributes to the literature by investigating the asymmetric impact and the time domain causal linkage between oil price fluctuations and real exchange rate in Algeria.